Cidades inteligentes: polissemias urbanas e pensamento complexo - César, Vivian Aparecida Blaso Souza Soares (2016)
This study evaluates minimum aspects of Production, Consumption and Environment during periods marked by UN warnings between 1972- Stockholm Conference, 2012- Rio+ 20 and 2015- cop21 in Paris. The complex thought of Edgar Morin runs this trajectory in which were needed efforts of reconnection of knowledges: engineering, smarts technologies, consumer behaviour, smart cities, sustainability, environment, and other networks that are hidden and what we seek to unravel. Structured in five meta themes: Sustainability, which discusses the genealogy of the concept and its incorporated levels by businesses, governments, the UN and civil society; Consumption and the Environment, which indicates who are consumers in contemporary society and shows how our relationship with the consumer is transforming our ways of living and housing; Sustainable technologies, smart cities and Smart cities lifestyle,reported through case studies and interviews in order to point outthe lack whatthis course for what really how as technologies to contribute to sustainability in cities.With the intention to expand the vision and perceptions of readers,we use the intertextualityfeature- visual,infographics, stories and essays, mixing fiction with photos and video "Smart Cities: Transformations in Progress" - nintroducing the reader to several narratives of sustainability in contemporary times